Efficacy and safety of topical glycopyrrolate in patients with facial hyperhidrosis: a randomized, multicentre, double‐blinded, placebo‐controlled, split‐face study. (9th June 2014) - Hyun, M.Y.; Son, I.P.; Lee, Y.; Choi, H.G.; Park, K.Y.; Li, K.; Kim, B.J.; Seo, S.J.; Kim, M.N.; Hong, C.K.
Abstract: Background: Although facial hyperhidrosis has been frequently associated with a diminished quality of life, various conservative modalities for its management are still far from satisfactory. Objective: To evaluate the antiperspirant efficacy and safety of the topical glycopyrrolate on facial hyperhidrosis at specified posttreatment intervals. Methods: Thirty‐nine patients with facial hyperhidrosis were enrolled and treated with 2% topical glycopyrrolate on one‐half of the forehead, whereas the other half of the forehead was treated with a placebo. All patients applied topical glycopyrrolate or placebo once a day for nine successive days. Each evaluation included weighing sweat and assessing the Hyperhidrosis Disease Severity Scale (HDSS) score and any adverse effects. Results: Compared with the placebo‐treated sides, topical glycopyrrolate‐treated sides showed a reduction in the rate of sweat production at the forehead of 25.16 ± 10.30% (mean ± SD) at 90 min after the first application (day 1), 29.63 ± 7.74% at 24 h after the first application (day 2) and 36.68 ± 11.41% at 24 h after eight additional successive daily applications (day 10) (all P  <   0.025). There was a little more decrease in HDSS score with the topical glycopyrrolate‐treated half of the forehead, but the difference was not statistically significant ( P  >   0.025). No serious adverse events were reported during the course of this study. Only one patient developed a transient headache after treatment. Conclusion: Topical glycopyrrolate application appears to be significantly effective and safe in reducing excessive facial perspiration.